1994
DOI: 10.1111/j.1467-971x.1994.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

The English language in Brunei Darussalam

Abstract: This paper attempts to give a brief overview of the variety of English spoken in the small sultanate of Brunei Darussalam in Northwest Borneo. After outlining the role played by English in the country and, in particular, in the Bruneian education system, the paper describes some of the grammatical and lexical features which differ most obviously from the imposed exonormative educational model, Standard British English. The transcribed interviews and examples included have been taken from a corpub of spoken dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…also Trudgill 1999b: 101) in the Inner Circle, but is also frequently found in the Outer Circle, in Singaporean English or Brunei English (cf. also Cane 1994: 354). Platt, Weber, and Ho (1984), who were the first scholars to summarize linguistic features ‘common to some or most of the New Englishes’, also note the tendency ‘not to mark the verb for third person singular in its present‐tense form’ (p. 85).…”
Section: The Case Of the ‘3rd Person ‐S’mentioning
confidence: 93%
“…also Trudgill 1999b: 101) in the Inner Circle, but is also frequently found in the Outer Circle, in Singaporean English or Brunei English (cf. also Cane 1994: 354). Platt, Weber, and Ho (1984), who were the first scholars to summarize linguistic features ‘common to some or most of the New Englishes’, also note the tendency ‘not to mark the verb for third person singular in its present‐tense form’ (p. 85).…”
Section: The Case Of the ‘3rd Person ‐S’mentioning
confidence: 93%
“…Cane (1993) claims that the variety of English spoken in Brunei fulfils all four of Platt et al's (1984:2-3) criteria for a "new" variety of English, hence that one can justifiably discuss Brunei English in the same way as Singapore or Malaysian English. Cane (1994) outlines similarities and differences between these three Southeast Asian Englishes.…”
Section: Theoretical Modelsmentioning
confidence: 97%
“…Cane () and Deterding and Salbrina () found that nouns that might be non‐count in standardised English are treated as countable in Brunei English. Cane (: 354) gives the following example where advice is being treated as a count noun: here's an advice for you all …”
Section: Grammatical Features Of Brunei Englishmentioning
confidence: 99%